Supporting factors in the selection of majors occupied by students - Putra, Ronald Wardey; Neviyarni, Neviyarni (Universitas Negeri Padang, 2023)
This research is motivated by the fact that many students feel that their current majors are not in accordance with their desires. This happens because of the supporting factors in choosing a major. The supporting factors in choosing the major include internal factors consisting of (1) talent, (2) interest, (3) motivation and external factors consisting of (1) the role of parents, (2) peers, (3) society. This research was conducted at SMK Negeri 2 Bukittinggi. This research is quantitative research with descriptive methods. The research sample amounted to 115 people. The instrument used is a questionnaire of supporting factors in choosing a Guttman Scale model major. The results showed that internal factors were in the high category, consisting of talent in the medium category, interest in the high category, and motivation in the medium category, while external factors were in the medium category, consisting of parental role factors in the high category, peer factors in the medium category, and community factors in the medium category.